Pro-stakeholders motivation: Uncovering a new source of motivation for business companies. (29th July 2016) - Bastons, Miquel; Mas, Marta; Rey, Carlos
Abstract: The motivation of employees is one of the main reasons why companies define mission statements and other declarations of commitment to the company's stakeholders. Research on organizational behavior has identified three main types of motivation: extrinsic, intrinsic and prosocial motivation. However, the three forms of motivation have hardly ever been considered together, nor has it been studied which motivation is linked to the stakeholders of business companies. The main contribution of this paper is to present an agent-stakeholders model of interaction which includes and integrates extrinsic, intrinsic and pro-stakeholders motivation, as a type of prosocial motivation related to the sense of contribution to benefitting the company's stakeholders. By basing the research on 119 Spanish companies it is verified that the three types of motivation are present in employee motivation. This finding has implications for management, as it presents the dimensions of the motivational task to be performed by managers.